Abstract ID: 136 Kompeito-shot system: Evaluation of the systematic error caused by beam incident angle using Monte Carlo simulation. (October 2017) - Tsuneda, Masato; Nishio, Teiji; Saito, Akito; Tanaka, Sodai; Kawahara, Daisuke; Suzuki, Tatsuhiko; Ozawa, Shuichi; Nagata, Yasushi
Abstract : We developed a novel verification system and method for verifying 3D/4D beam alignment. The purpose of this study is to evaluate the systematic error of the measurement system we developed using Particle and Heavy Ion Transport code System (PHITS)[1] . Our newly method enables to quantitatively and directly evaluate the gantry rotation axis as angle information. In short, this method enables to measure directly sagging angle of gantry head. This system was composed of truncated cone-shaped mirror, column-typed plastic scintillator (Co-typed PS) and a CCD camera. Co-typed PS emitted the scintillation light generated by photon beams, and the static image of the scintillation light was measured using the camera through the mirror. We obtained a simulation image that is similar to measurement image. Therefore, we calculated the energy deposition in Co-typed PS by PHITS (ver. 2.84) Monte Carlo simulation code. Photon beams with TrueBeam 6 MV energy spectrum was irradiated for Co-typed PS that placed on center of truncated cone shaped mirror. We created 2D simulation image using geometric transformation from 3D voxel data. The calculation grid was 0.5 × 0.5 × 0.5 mm 3 . And we compared the measurement and simulation images to convert energy deposit to light intensity. We analyzed these simulation images using analysis algorithm that we developed and evaluated the systematic error. We could obtain the simulation image without taking into consideration of the optical element, manufacture error and setup error. The relationship between irradiated beam angle (IA) and calculated beam angle (CA) had good linearity and accuracy. However, the difference between IA and CA tended to increase with increasing in irradiated angle and the maximum difference was −0.8 degree. This systematic error was caused by the scintillation light integrated in all layer of Co-typed PS. We calculated simulation image using one-layer of Co-typed PS and compared the difference. The difference was decreased to ±0.1 degree. We developed the simulation image generator system using PHITS and evaluate the systematic error.